Development and validation of a recombinant human TNF-α based ELISA to detect and quantify adalimumab - Dinesh Kumar Saini; Manjunath S. Devaramani; Hemalakshmi Shanmugavel; Syeda Zuhin Tabassum; Kiran Kumar Mudnakudu-Nagaraju; Jalahalli Mariswamy Siddesha; Radhakrishna Shetty (Biochemistry and Biophysics Reports)
Adalimumab, a humanized IgG1 monoclonal antibody is currently used to treat inflammatory diseases. However, a sensitive, in-house ELISA for evaluating inter- and intra-individual pharmacokinetic variability of adalimumab remains limited. In this study, an ELISA was developed to measure adalimumab levels, using recombinant human TNF-α (rhTNF-α) as capture antibody. Initially, surface plasma resonance showed acceptable binding kinetics (KD) of 2.38x10−07 nM for adalimumab. Next, a standard curve of adalimumab (1.54 ng/ml to 300 ng/ml), with five quality control points (5.2, 16, 27, 150, and 200 ng/ml) was evaluated for inter and intra-assay accuracy and precision, using serum matrix, by four independent validations. The linear range of the validated assay was 5.2 ng/ml to 200 ng/ml, upper limit of quantification (ULOQ) and lower limit of quantification (LLOQ) were 200 ng/ml and 5.2 ng/ml, respectively. The assay specificity was validated by testing cross-reactivity of rituximab with rhTNF-α, which was found to be non-reactive. Further, the hook effect was over-ruled by diluting the highest concentration of adalimumab tested to assay linear range, and dilution integrity was observed for entire concentrations within linear range (%RE ≤ 20 %), as recommended by European Medicines Agency. Collectively, this rhTNF-α binding-based ELISA method is highly sensitive, reproducible, and useful for monitoring adalimumab.